FROM REGULATION TO COMMODIFICATION: A CRITICISM OF THE LEGAL POLITICS OF HALAL CERTIFICATION IN INDONESIA - Buhari Imran; Zuhrinal M. Nawawi (Pena Cendekia Insani, 2026)
This research examines the political and legal transformation of halal certification in Indonesia using the Critical Legal Studies (CLS) approach. In the last decade, halal certification has no longer served solely as an instrument of moral protection and legal certainty for Muslim consumers, but has transformed into a political and economic instrument operating within the logic of the global market. Thru normative-empirical analysis, this study reveals that halal bureaucratization thru the involvement of the Halal Product Assurance Agency (BPJPH) and the Indonesian Ulema Council (MUI) creates tension between legal and moral authorities. This phenomenon shows how religious law is institutionalized by the state and reduced to an administrative mechanism laden with economic interests and political legitimacy. Furthermore, the research found that halal regulations also contribute to the commodification of religious values, where piety and halalness become market symbols and tools for nation branding. This process has implications for the emergence of unequal access for micro and small business actors (MSMEs), who find it difficult to bear the costs and complex certification procedures. Within the framework of CLS, this condition indicates that legal norms operate within a power structure that maintains social and economic hierarchies. This research underscores the need for a more emancipatory reform of halal regulations, emphasizing substantive justice, equitable access, and integration between the values of maq??id al-syar? ‘ah and modern social justice so that halal certification does not lose its spiritual meaning as a means of public welfare.